Effects of Sequence Mixing of Stereocomplex Poly(Lactic Acid)/Propylene-Ethylene Copolymer Blends for Plastic Packaging - Wadputi, Jetawat; Wiriyakitkaset, Palerat; Somnuake, Pattara; Teeka, Wikoramet; Wacharawichanant, Sirirat (Engineering Access, 2025)
This work examines the effect of sequence mixing stereocomplex poly(lactic acid) (Sc-PLA) on the thermal and mechanical properties of Sc-PLA/elastomer blends. In this study, PLA was melted and blended with poly(D-lactic acid) (PDLA) in an internal mixer at the ratios of 95/5, 90/10, and 85/15 by weight, and then the sample was molded by compression molding. The most significant improvement was found in blending 10 wt% PDLA. The results show the highest Young’s modulus at 2200 MPa from the neat PLA at 1800 MPa. The stereocomplex PLA/PDLA (Sc-PLA/PDLA) at proportion 90/10 wt% by being chosen blended with propylene-ethylene copolymer (PEC) elastomer to study the effect of sequence mixing of Sc-PLA/PDLA/elastomer blends on thermal and mechanical properties and the amount of PEC elastomer was fixed at 10 wt% in the mixture. The mechanical properties show results at 10% break elongation of Sc-PLA/PDLA/PEC blends that is higher than the others, which confirmed that PEC elastomer, which is improved features of Sc-PLA/PDLA flexibility blends and sequence mixing of PLA stereocomplex/elastomer blends affected to the mechanical properties. The result of thermal properties shows the sequence mixing of PLA stereocomplex/elastomer blends does not affect the melting temperature but affects the enthalpy (∆Hm-∆Hc) by Sc-PLA/PEC add PDLA significant decreasing at 23 J/g °C by the other conditions show about 28 J/g °C. It supports the sequence of mixing at Sc-PLA/PDLA/PEC mixed simultaneously, which is the best. The analysis results show that sequence mixing significantly affects polymer blends’ properties, which can be applied to industrial processes.